The effect of board structure and institutional ownership structure on earnings management - Wong, Shi Yang; Loo, Sin Chun; Ramadilli Mohd, Shamsher Mohamad (Faculty of Economics and Management, Universiti Putra Malaysia, 2009)
The study examines the role of outside directors and institutional shareholders in constraining the earnings management activities. A sample of 613 firms from construction, industrial products and consumer products sectors were selected from the main board. The time period covered for this study was from year 2001 to 2003. Modified Jones Model with cross sectional approach was employed in this study. The finding shows that magnitude of earnings management in Malaysian listed firms has approximately 16% of prior year total assets. Most firms manage the earnings upward rather than downwards. No relationship was observed between the degree of earnings manipulation and the proportion of outside directors and institutional shareholders. However, there is weak evidence to show that outside directors have some effect in curbing the earnings management in the construction sector. Adding more outside directors in the board and having institutional shareholders may not be able to reduce earnings management practices if the ownership of a firm is highly concentrated and the process of selecting outside directors is not clearly stated and transparent.